Noncardiac Vascular Toxicities of Vascular Endothelial Growth Factor Inhibitors in Advanced Cancer: A Review - Keefe, Dorothy (AlphaMed Press, 2011)
SUMMARY. The introduction of molecularly targeted anticancer therapies has brought the promise of longer survival times for select patients with cancers previously considered untreatable. However, it has also brought new toxicities that require understanding and management, sometimes for long periods of time. Vascular endothelial growth factor inhibitors are associated with a broad range of adverse effects, with vascular toxicity being particularly serious. This review focuses on the current understanding of the pathophysiology and mechanisms of macrovascular toxicities (hypertension, hemorrhage, and thromboembolism), their incidence and severity, the current clinical management, and implications in the advanced cancer setting. Movement of these agents into the early disease setting will alter the impact of these toxicities. SEARCH STRATEGY AND SELECTION CRITERIA. Information for this review was collected by searching PubMed/Medline and American Society of Clinical Oncology abstract databases. The medical subject heading terms used included toxicity, hypertension, thromboembolism, hemorrhage, intestinal perforation, risk factors, pharmacokinetics, and metabolism, combined with free text search terms including, but not limited to, VEGF inhibitor*, bevacizumab, sunitinib, and sorafenib. Articles published in English before March 2010 were included, in addition to information from case reports and pharmaceutical agent package inserts.